Diradicals Produce Ambipolar Transistors: What and Why - Casado-Cordón, Juan; Moles Quintero, Sergio; Kato, Shin-ichiro; Negri, Fabrizia (ISNA-19, 2022)
organic conjugated diradicals have gaining interest in the recent times given their uses in different formats of electronic applications encompassing OFETs,1 non-linear optical dyes, chromophores for singlet fission in OPV,2 etc. Our recent interests have turned into the role of their open-shell structures and their impact in the stabilization of +1, -1 charges. Since the first studies in fused planar diradicals, we were fascinated by the fully reversible and almost perfect oxidation/reduction mirror-like shapes of their cyclic voltammetries (i.e., uncommon in the organic field, in Fig. 1).3 This aimed us to test the ambipolar charge transport character of diradicals in OFETs and discovered that some particular diradicals are able to transport both kind of charges, holes and electrons, with similar mobility, or balanced p-n mobility.
Diradicals Produce Ambipolar Transistors: What and Why
Keywords: Superconductores orgánicos - Congresos; Organic transistors; Diradicals